Dealing with Politics for Money and Power in Infrastructure - Benitez, Daniel; Estache, Antonio; Soreide, Tina (2012)
Policy recommendations for infrastructure provision usually build on a well-established understanding of best practice for sector governance. Too rarely are they adapted to the country-specific political environment even if this is an area where policy choices are likely to be subject to private agendas in politics. The fact that such private agendas are often ignored goes a long way toward explaining why infrastructure policies fail and why best practice can be counterproductive. While non-benevolence and rent-seeking are well described in the literature and anecdotes abound, there is only limited consideration of how the different incentive problems in politics impede policy improvements in infrastructure. This paper addresses why politics in infrastructure cannot be ignored, drawing on theoretical results and a systematic review of experiences. It reviews how different private agendas in politics will have different impacts for sector-governance decisions -- and hence service delivery. The concept of best practice in policy recommendations should be reconsidered in a wide perspective and allow for tailored solutions based on an understanding of the given incentive problems. Policy recommendations should take into account how coordination trade-offs may complicate efforts to reduce the possible impact of private agendas on infrastructure policy decisions. Although more transparency linked to service delivery indicators is a "safe" recommendation, it is also clear that the demand for good governance will not be sufficient to secure political accountability in a sector with huge vested interests combined with complicated funding schemes and complex contracts.